Diagnosis of pediatric tuberculosis using The Indonesian National Concencus for Pediatric Tuberculosis - Heda Melinda D. Nataprawira; Cissy B. Kartasasmita; Oma Rosmayudi; Hudiyati Agustini (Paediatrica Indonesiana, 2001)
Diagnosing tuberculosis (TB) in children correctly is critical to appropriate treatment. However, diagnosing TB in children may be difficult and can be imprecise. As our national TB control program has not adequately covered TB in children and adult TB cases still in high rank, our national consensus for pediatric population may facilitate TB diagnosed especially in the field. This cross sectional study as part of longitudinal cohort study of epidemiology of Respiratory Syncitial Virus (RSV) in Indonesia (still ongoing) was conducted to know whether criteria used in the algorithm in the consensus compatible to suspected TB diagnosis. The study covered 1000 children under five randomly selected in two districts (Cikutra and Ujung Berung Indah) located in West Java. By using algorithm of The Indonesian National Consensus For Pediatric Tuberculosis (INCPT) with history of known or suspected adult source of TB or early reaction of BCG vaccination and certain general clinical symptoms associated TB as entry criteria for a higher index of suspicion, we diagnosed suspected TB in 57 children. We found that, history of known or suspected adult source of TB and certain general clinical symptoms are two main criteria for suspected TB diagnosis. It appeared that Mantoux test gave a smallest contribution to the diagnosis of suspected TB in the field. No other criterium except known or suspected adult source of TB fulfilled for other five children and prophylactic treatment for TB were given. Those children with suspected TB were given oral anti-tuberculosis (OAT) by Directly Observed Treatment Short course (DOTS) done by local trained persons.